Replicated throughfall exclusion experiment in an Indonesian perhumid rainforest: wood production, litter fall and fine root growth under simulated drought. (27th March 2014) - Moser, Gerald; Schuldt, Bernhard; Hertel, Dietrich; Horna, Viviana; Coners, Heinz; Barus, Henry; Leuschner, Christoph
Abstract Climate change scenarios predict increases in the frequency and duration of ENSO‐related droughts for parts of South‐East Asia until the end of this century exposing the remaining rainforests to increasing drought risk. A pan‐tropical review of recorded drought‐related tree mortalities in more than 100 monitoring plots before, during and after drought events suggested a higher drought‐vulnerability of trees in South‐East Asian than in Amazonian forests. Here, we present the results of a replicated (n = 3 plots) throughfall exclusion experiment in a perhumid tropical rainforest in Sulawesi, Indonesia. In this first large‐scale roof experiment outside semihumid eastern Amazonia, 60% of the throughfall was displaced during the first 8 months and 80% during the subsequent 17 months, exposing the forest to severe soil desiccation for about 17 months. In the experiment's second year, wood production decreased on average by 40% with largely different responses of the tree families (ranging from −100 to +100% change). Most sensitive were trees with high radial growth rates under moist conditions. In contrast, tree height was only a secondary factor and wood specific gravity had no influence on growth sensitivity. Fine root biomass was reduced by 35% after 25 months of soil desiccation while fine root necromass increased by 250% indicating elevated fine root mortality. Cumulative aboveground litter production was not significantly reduced in this period. The trees from this Indonesian perhumid rainforest revealed similar responses of wood and litter production and root dynamics as those in two semihumid Amazonian forests subjected to experimental drought. We conclude that trees from paleo‐ or neotropical forests growing in semihumid or perhumid climates may not differ systematically in their growth sensitivity and vitality under sublethal drought stress. Drought vulnerability may depend more on stem cambial activity in moist periods than on tree height or wood specific gravity.